1995
DOI: 10.1083/jcb.131.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged induction of p21Cip1/WAF1/CDK2/PCNA complex by epidermal growth factor receptor activation mediates ligand-induced A431 cell growth inhibition.

Abstract: Abstract. Proliferation of some cultured human tumor cell lines bearing high numbers of epidermal growth factor (EGF) receptors is paradoxically inhibited by EGF in nanomolar concentrations. In the present study, we have investigated the biochemical mechanism of growth inhibition in A431 human squamous carcinoma cells exposed to exogenous EGF. In parallel, we studied a selected subpopulation, A431-F, which is resistant to EGF-mediated growth inhibition. We observed a marked reduction in cyclin-dependent kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
1

Year Published

1998
1998
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 44 publications
(72 reference statements)
12
77
1
Order By: Relevance
“…Cell cycle distribution analysis with propidium iodide was previously described (Fan et al, 1995). For analysis with mithramycin staining, an aliquot of 2610 6 cells was incubated with 2 ml of 0.1% nonidet P-40 in PBS for 5 min, followed by ®xation with the addition of 0.7 ml of 4% formaldehyde in PBS and gentle shaking of the cells at 48C for 15 min.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Cell cycle distribution analysis with propidium iodide was previously described (Fan et al, 1995). For analysis with mithramycin staining, an aliquot of 2610 6 cells was incubated with 2 ml of 0.1% nonidet P-40 in PBS for 5 min, followed by ®xation with the addition of 0.7 ml of 4% formaldehyde in PBS and gentle shaking of the cells at 48C for 15 min.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Cells were lysed as previously described (Fan et al, 1995). Speci®c signals were visualized by the ECL chemoluminescence detection kit (Amersham, Arlington Heights, IL, USA).…”
Section: Immunoblot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Low doses of radiation induce expression of p21 Cip-1 via a p42 MAP kinase dependent mechanism High dose irradiation of cells has been shown to induce expression of the cyclin dependent kinase (cdk) inhibitor protein p21 , and other studies have demonstrated that growth factors can induce p21 Cip-1 expression via a p42 MAP kinase dependent mechanism (Pumiglia and Decker, 1997;Whalen et al, 1997;Lloyd et al, 1997;Fan et al, 1995;Missero et al, 1996;Macloed et al, 1995;Liu et al, 1996;Deng et al, 1995;Van den Heuvel and Harlow, 1993;Lees et al, 1993;Brugarolas et al, 1995). However, it has been suggested that radiation and growth factors induce Time Course of inhibition of GSK3 activity after 1 Gy exposure of A431 cells A431 cells (150 mm dishes) were exposed to 1 Gy (1.8 Gy/min) and at speci®ed time points media aspirated and the plates snap frozen.…”
Section: Low Doses Of Radiation Cause Increases In C-jun Serine 63 Phmentioning
confidence: 99%
“…Acute activation of the MAP kinase cascade by growth factors has been shown to potentiate proliferation, whereas chronic elevation of MAP kinase activity has been demonstrated to be cytoprotective against irradiation (Canman et al, 1995), and to inhibit DNA synthesis potentially via induction of the cyclin dependent kinase (cdk) inhibitor protein p21 Cip-1 (Pumiglia and Decker, 1997;Wixler et al, 1996;Traverse et al, 1994;Whalen et al, 1997;Lloyd et al, 1997;Fan et al, 1995;Missero et al, 1996;Macloed et al, 1995;Liu et al, 1996;Deng et al, 1995). The cdk inhibitor protein p21 Cip-1 can also be induced in response to radiation exposure of cells, and cultured ®broblasts from p21 Cip-1`k nock-out' mice which cannot express p21 have been demonstrated to be more radiosensitive than wild type cells, demonstrating that expression of this molecule is cytoprotective against radiation (Missero et al, 1996;Macloed et al, 1995;Liu et al, 1996;Deng et al, 1995).…”
Section: Introductionmentioning
confidence: 99%